2020
DOI: 10.1002/art.41173
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA Methylation of Networked Signaling, Transcriptional, Innate and Adaptive Immunity, and Osteoclastogenesis Genes and Pathways in Gout

Abstract: Objective. In gout, autoinflammatory responses to urate crystals promote acute arthritis flares, but the pathogeneses of tophi, chronic synovitis, and erosion are less well understood. Defining the pathways of epigenomic immunity training can reveal novel pathogenetic factors and biomarkers. The present study was undertaken to seminally probe differential DNA methylation patterns utilizing epigenome-wide analyses in patients with gout.Methods. Peripheral blood mononuclear cells (PBMCs) were obtained from a San… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Our data from mouse has clinical implications since we demonstrated that individuals with gout display lower levels of blood glucose levels when compared to those with HU but not gout. Moreover, prior studies have shown 75 transcription factor motifs associated with hypomethylated differential methylation loci regions in gout vs. healthy controls (48) including those that belong to MEF2C, NFATC2, JUN and FOS, HIF1A, MYC-MAX and circadian clock regulators CLOCK and BHLHLE40. Interestingly, we find upregulation of Fosb, Fosl1, Fosl2, Hif1a, Max and Bhlhe40 -but not Mef2c that was downregulated or Nfatc2 that was unaffected-in PBMC from mice injected with MSUc indicating that similar signaling pathways might be involved in the activation of PBMC in patients with gout during flares.…”
Section: Discussionmentioning
confidence: 99%
“…Our data from mouse has clinical implications since we demonstrated that individuals with gout display lower levels of blood glucose levels when compared to those with HU but not gout. Moreover, prior studies have shown 75 transcription factor motifs associated with hypomethylated differential methylation loci regions in gout vs. healthy controls (48) including those that belong to MEF2C, NFATC2, JUN and FOS, HIF1A, MYC-MAX and circadian clock regulators CLOCK and BHLHLE40. Interestingly, we find upregulation of Fosb, Fosl1, Fosl2, Hif1a, Max and Bhlhe40 -but not Mef2c that was downregulated or Nfatc2 that was unaffected-in PBMC from mice injected with MSUc indicating that similar signaling pathways might be involved in the activation of PBMC in patients with gout during flares.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation sequencing further confirmed that the promoter regions of Runx2 and OSX exhibited significantly decreased DNA methylation levels, and the DNA methylation levels were significantly correlated with gene expression (Zhang R. P. et al, 2011). Inhibition of FIGURE 2 | Molecular mechanism of DNA methylation (Yang and Duan, 2016;Letarouilly et al, 2019;Ahmed et al, 2020;Wang et al, 2020;Xu et al, 2020). DNA methylation modification is mainly controlled by DNMT proteins.…”
Section: Runx2 and Osxmentioning
confidence: 91%
“… Molecular mechanism of DNA methylation ( Yang and Duan, 2016 ; Letarouilly et al, 2019 ; Ahmed et al, 2020 ; Wang et al, 2020 ; Xu et al, 2020 ). DNA methylation modification is mainly controlled by DNMT proteins.…”
Section: Dna Methylation and Opmentioning
confidence: 99%
See 1 more Smart Citation
“…Gouty inflammation is an acute and painful type of arthritis caused by the precipitation of monosodium urate (MSU) in the joints. The phagocytosis of MSU by macrophages triggers NLRP3 inflammasome activation, resulting in secretion of IL-1β which plays a key role in the inflammatory cascade ( Bach et al., 2019 ; Kingsbury et al., 2011 ; Liu-Bryan, 2010 ; Shin et al., 2019 ; Steiger and Harper, 2014 ; Wang et al., 2020 ). In addition, MSU could directly activate T cells in an antigen-independent manner in gouty arthritis ( Webb et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%